2021
DOI: 10.18388/abp.2020_5639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-fat diets on inflammation and antioxidant status in rats : comparison between palm olein and olive oil

Abstract: Abstract Palm olein (PO) and olive oil (OO) are widely consumed in the world. PO is considered harmful to health, whereas OO is considered healthy. The aim of the study was to compare the effects of consumption of these oils on antioxidant status and inflammation in rats. This was an experimental study in male wistar rats fed a diet containing 30% of each oil. Rats had free access to food and water. After being fed for 12 weeks, animals were sacrificed and liver and aortic blood were collected. Plasma wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…NO scavenging by superoxide anion (O 2 − ) could be increased leading to increased peroxynitrite production and hypercontractility. Consistent with this hypothesis and with a previous study [60], on the one hand, we observed a decreased SOD activity with PO and lard diet. On the other hand, the effect of tempol on Pheinduced contractile response was significantly decreased with PO and lard diets, indicating that O 2 − is not the main ROS involved in vascular tone.…”
Section: Discussionsupporting
confidence: 93%
“…NO scavenging by superoxide anion (O 2 − ) could be increased leading to increased peroxynitrite production and hypercontractility. Consistent with this hypothesis and with a previous study [60], on the one hand, we observed a decreased SOD activity with PO and lard diet. On the other hand, the effect of tempol on Pheinduced contractile response was significantly decreased with PO and lard diets, indicating that O 2 − is not the main ROS involved in vascular tone.…”
Section: Discussionsupporting
confidence: 93%
“…Olive oil, RPO, and CPO have oleic acid values of 66.4%, 39.2%, and 37.4% ( Kumar and Krishna, 2014 ; Mancini et al., 2015 ; Orsavova et al., 2015 ). Furthermore, Djohan et al. (2021) found that POl has anti-inflammatory properties comparable to olive oil, with no significant changes in interleukin-6 gene expression between the two.…”
Section: Palm Oil and Healthmentioning
confidence: 94%
“…(2019) RPO, olive oil 55% energy from RPO 40 male Wistar rats Both RPO and olive oil diets ↑ myokines gene expression Gauze-Gnagne et al. (2020) POl, olive oil 55% energy from POl 24 male Wistar rats No significant changes in interleukin-6 and oxidative stress parameters Djohan et al. (2021) RPO - 6 male Wistar rats ↓ fibrinogen, ↑ antithrombin levels Pereira et al.…”
Section: Palm Oil and Healthmentioning
confidence: 99%
“…The "minor" components of palm oil are what give it its nutritional advantages, which are related to its antioxidant power [31]. Numerous research studies on animals have emphasized the antioxidant properties of PO tocotrienols.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study demonstrate that PO still retains its antioxidant effects despite the loss of carotenoids and micro-constituents including flavonoids and phenolic acids after refining. This might be because tocotrienols, potent free radical scavengers, are added to PO during refining, enhancing their antioxidant properties [31].…”
Section: Discussionmentioning
confidence: 99%